TRANSFORMASI PONDOK PESANTREN DI ERA DIGITAL: DAMPAK POSITIF MULTIMEDIA DALAM PENDIDIKAN, DAKWAH, DAN KEMANDIRIAN SANTRI - Muhammad Hafidz Khusnadin; Aria Septi Anggaira; Rohimin Al'Asror (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In Central Lampung Regency, Islamic boarding schools (pondok pesantren) have undergone rapid transformation by integrating multimedia as an essential part of education, da'wah, and the development of students' independence. The objective of this study is to explore the utilization of multimedia in enhancing the quality of education in Islamic boarding schools in the digital era and to examine the role of multimedia in supporting the effectiveness of da'wah in these institutions. This research employs a qualitative method with a descriptive approach. The findings indicate that the transformation of pesantren through multimedia has significantly contributed to shaping independent, competitive students who are well-prepared to face challenges in the digital era while maintaining the core Islamic values that underpin education in pesantren.